2009
DOI: 10.1177/112067210901900409
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Syndrome-Related Quality of Life in Glaucoma Patients

Abstract: Patients with topically treated glaucoma present DES more often than a similar control group (p=0.01). The presence of DES negatively influences the patient's QOL. The patients with glaucoma's ocular surface status should be evaluated regularly to ensure the timely detection and treatment of pathologic signs on the ocular surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
1
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(158 citation statements)
references
References 39 publications
12
133
1
12
Order By: Relevance
“…The lack of correlation between signs and symptoms of OSD has been attributed to BAK-preserved eyedrops decreasing corneal sensitivity (38,39), perhaps by reducing sub-basal corneal nerve density (37). While some authors have not been able to correlate the number of preservative-containing eyedrops used with symptoms (17,19,20,23,25,40), others have detected such correlation (18,21,22,24). What has been clearly established is that effects of the glaucoma treatment burden can include OSD symptoms such as irritation, burning, dryness, photophobia, or foreign body sensation.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correlation between signs and symptoms of OSD has been attributed to BAK-preserved eyedrops decreasing corneal sensitivity (38,39), perhaps by reducing sub-basal corneal nerve density (37). While some authors have not been able to correlate the number of preservative-containing eyedrops used with symptoms (17,19,20,23,25,40), others have detected such correlation (18,21,22,24). What has been clearly established is that effects of the glaucoma treatment burden can include OSD symptoms such as irritation, burning, dryness, photophobia, or foreign body sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies are showing a strong correlation between the number of IOP-lowering medications used and the presence of dry eye [8,16,17]. Study by Rossi et al [16] described the prevalence of OSD and they wanted to assess quality of life in subjects with glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Rossi et al [16] described the prevalence of OSD and they wanted to assess quality of life in subjects with glaucoma. In this study 40% of patients using 2 or 3 antiglaucoma medications had symptoms of OSD, which is in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, BAK causes instability of the tear layer, loss of goblet cells, conjunctival squamous metaplasia, apoptosis, disruption of the corneal epithelial barrier and subclinical inflammation of the ocular surface. Several epidemiological studies have confirmed that about half of the patients treated with topical glaucoma medication have signs and ⁄ or symptoms of ocular surface disease (Jaenen et al 2007;Leung et al 2008;Rossi et al 2009;Fechtner et al 2010) and that this prevalence is higher in patients with glaucoma using preserved drops compared with patients using preservative-free drops (Pisella et al 2002). Much less is known about Benzalkonium chloride induces anterior chamber inflammation in previously untreated patients with ocular hypertension as measured by flare meter: a randomized clinical trial a potential effect of BAK on the deeper structures of the eye in vivo, although observations made in vitro on human trabecular meshwork cell lines and lens epithelial cells suggest a detrimental effect of BAK on these structures (Samples et al 1989;Hamard et al 2003;Goto et al 2003).…”
Section: Introductionmentioning
confidence: 99%